THE OPTICAL PROPERTIES OF MULTILAYER PERIODIC STRUCTURES BaTiO3:Eu/SiO2 - D. A. Parafinyuk; N. V. Gaponenko; T. F. Raichenok (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
This paper presents the study of the optical properties of multilayer periodic structures, such as Bragg reflector, with different synthesis conditions. Transmission, reflection, luminescence, luminescence excitation spectra and kinetics of luminescence are presented for the Bragg reflectors formed on quartz with 6 and 12 alternating layers BaTiO3:Eu/SiO2. The structures demonstrate photonic band gap and its long wavelength shift with increasing number of layers. Europium luminescence with the most intensive band at 615 nm is observed from the structures. A decrease in the luminescence intensity with increasing the number of pairs of the layers in the structure is observed.